Incarcerated Grynfelt-Lesshaft's giant lumbar hernia: a case report - Jaiswal, Anurag; Bhati, Sawan; Sumit; Singh, Paritosh; Gupta, Shishir (International Journal of Research in Medical Sciences, 2023)
A uncommon posterior abdominal wall defect called the Grynfeltt-Lesshaft hernia permits the herniation of retro and intraperitoneal tissues via the upper lumbar triangle. We describe a case of a post-menopausal woman who visited the surgical OPD because of a bulge that was steadily growing in the right lumbar area. She had a history of spinal tuberculosis and underwent computed tomography (CT) guided aspiration of a paravertebral abscess and surgical fixation of vertebrae. During the initial clinical examination, the swelling resembled a large lipoma, but other potential diagnoses considered were an incisional hernia, large lipoma, abscess, or hematoma. Ultrasonography was inconclusive in differentiating due to the large size and limited visibility. Consequently, contrast-enhanced computed tomography (CECT) scans of the abdomen revealed a substantial defect in the right lumbar area with herniation of the small bowel, large bowel, and omental fat. The diagnosis of a right Grynfelt hernia was established, and the patient was referred for surgical repair. Preoperatively, the hernia was classified as a type "A" lumbar hernia, according to Moreno-Egea et al classification. For the diagnosis of lumbar hernia and surgical planning, computed tomography (CT) is the most commonly used imaging modality. It allows for accurate visualization and assessment of the hernia, aiding in both the diagnosis and the planning of the surgical procedure.